2012
DOI: 10.1073/pnas.1217609110
|View full text |Cite
|
Sign up to set email alerts
|

Diverse specificity and effector function among human antibodies to HIV-1 envelope glycoprotein epitopes exposed by CD4 binding

Abstract: The HIV-1 envelope glycoprotein (Env) undergoes conformational transitions consequent to CD4 binding and coreceptor engagement during viral entry. The physical steps in this process are becoming defined, but less is known about their significance as targets of antibodies potentially protective against HIV-1 infection. Here we probe the functional significance of transitional epitope exposure by characterizing 41 human mAbs specific for epitopes exposed on trimeric Env after CD4 engagement. These mAbs recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
344
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 145 publications
(362 citation statements)
references
References 94 publications
(117 reference statements)
18
344
0
Order By: Relevance
“…infected individuals and to mediate potent ADCC responses (13,14,18,(20)(21)(22)(23)(24)(25)(26). Therefore, our results raise the intriguing possibility that histidine 375 present in the predominant strain replicating in Thailand might have contributed to the efficacy of the trial by spontaneously exposing epitopes recognized by ADCC-mediating antibodies elicited by the RV144 vaccine regimen.…”
Section: Figmentioning
confidence: 79%
See 2 more Smart Citations
“…infected individuals and to mediate potent ADCC responses (13,14,18,(20)(21)(22)(23)(24)(25)(26). Therefore, our results raise the intriguing possibility that histidine 375 present in the predominant strain replicating in Thailand might have contributed to the efficacy of the trial by spontaneously exposing epitopes recognized by ADCC-mediating antibodies elicited by the RV144 vaccine regimen.…”
Section: Figmentioning
confidence: 79%
“…The gp120 outer-domain-specific 2G12 and the anti-gp41 10e8 antibodies were obtained from the NIH AIDS and Research and Reference Reagent Program. Anti-gp120 cluster A antibody A32 and coreceptor binding site antibody 17b were previously reported (14,24,54,55). A32-blockable conformational epitope ADCC-mediating antibodies isolated from recipients of the RV144 ALVAC-HIV AIDSVAX B/E vaccine (CH29, CH38, CH40, CH51, CH52, CH54, CH77, CH80, CH81, CH89, CH91, and CH94) were previously described (14,26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A high-dose SHIV162P3 challenge study showed that immunisation with gp120-CD4 fusion protein (FLSC) elicited titres of CD4i specific Abs [38], in particular coreceptor binding site specific antibodies [39] that correlated with control of viremia. In what is a presumably more physiological repeated low dose challenge of animals vaccinated across varied FLSC/adjuvant regimens, protection from acquisition was correlated with CD4i antibody and ADCC activity, but only in individuals with low CD4 T cell responses.…”
Section: In Vivo Studies I: Macaque and Mouse Modelsmentioning
confidence: 99%
“…Target cells may also be sensitised using inactivated virus [38]. Standard natural cytotoxicity assays assays measure the release of chromium, 51 Cr, from isotope-labelled unosponised target cells in the presence of NK cells.…”
Section: Cell Based Functional Assays For Fcr Activating Antibodiesmentioning
confidence: 99%